ENHANCING STOCK MARKET AWARENESS IN RURAL AND SEMI-URBAN AREAS: A CASE STUDY OF CHICKBALLAPUR AND CHITRADURGA - Pasha, Mujammil; K, Leelavathi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The stock market is a cornerstone of economic growth and individual wealth generation. However, in rural and semi-urban areas such as Chickballapur and Chitradurga, awareness and participation in the stock market remain low. This study explores the current state of stock market awareness in these regions, identifies barriers to participation, and proposes solutions to enhance financial literacy. Using a mixed-method approach, the study highlights the need for community-based interventions, digital inclusion, and policy support to bridge the awareness gap.